Translation Ideologies of The Culture Specific Items in Indonesian Translation “Of Mice and Men” Novel - Martinda Intan Permatahati; Abdurrachman Faridi; Mursid Saleh (Universitas Negeri Semarang, 2021)
Translating a novel is an activity that requires making a great number of decisions and consequently carries many risks of making mistakes. All decisions made by translators in the translation process depend on the translator's ideology. The focus of this research is the ideology of the Indonesian translation of the novel